Endoxifen downregulates AKT phosphorylation through protein kinase C beta 1 inhibition in ERα+ breast cancer - Swaathi Jayaraman; Xinyan Wu; Krishna R. Kalari; Xiaojia Tang; Mary J. Kuffel; Elizabeth S. Bruinsma; Shahrzad Jalali; Kevin L. Peterson; Cristina Correia; Rachel A. Kudgus; Scott H. Kaufmann; Santosh Renuse; et al. (npj Breast Cancer, 2023)
Abstract Endoxifen, a secondary tamoxifen metabolite, is a potent antiestrogen exhibiting estrogen receptor alpha (ERα) binding at nanomolar concentrations. Phase I/II clinical trials identified clinical activity of Z-endoxifen (ENDX), in endocrine-refractory metastatic breast cancer as well as ERα+ solid tumors, raising the possibility that ENDX may have a second, ERα-independent, mechanism of action. An unbiased mass spectrometry approach revealed that ENDX concentrations achieved clinically with direct ENDX administration (5 µM), but not low concentrations observed during tamoxifen treatment (<0.1 µM), profoundly altered the phosphoproteome of the aromatase expressing MCF7AC1 cells with limited impact on the total proteome. Computational analysis revealed protein kinase C beta (PKCβ) and protein kinase B alpha or AKT1 as potential kinases responsible for mediating ENDX effects on protein phosphorylation. ENDX more potently inhibited PKCβ1 kinase activity compared to other PKC isoforms, and ENDX binding to PKCβ1 was confirmed using Surface Plasma Resonance. Under conditions that activated PKC/AKT signaling, ENDX induced PKCβ1 degradation, attenuated PKCβ1-activated AKTSer473 phosphorylation, diminished AKT substrate phosphorylation, and induced apoptosis. ENDX’s effects on AKT were phenocopied by siRNA-mediated PKCβ1 knockdown or treatment with the pan-AKT inhibitor, MK-2206, while overexpression of constitutively active AKT diminished ENDX-induced apoptosis. These findings, which identify PKCβ1 as an ENDX target, indicate that PKCβ1/ENDX interactions suppress AKT signaling and induce apoptosis in breast cancer.